Ojek Online, Pekerja atau Mitra? - Oka Halilintarsyah (Jurnal Persaingan Usaha, 2021)
Keberadaan ojek online masih menimbulkan perdebatan apakah merupakan pekerja atau mitra. Dalam putusan Supreme Court U.K., Pekerja ojek online yang dikenal juga sebagai gig worker telah diputuskan merupakan pekerja. Hasil penelitian menunjukkan bahwa peraturan perundang-undangan Indonesia belum dapat mengakomodir keberadaan ojek online sebagai pekerja. Namun, perlu ada perlindungan bagi mitra ojek online terutama dalam hal keselamatan dan keamanan serta pendapatan. Pemerintah perlu menentukan arah kebijakan ketenagakerjaan untuk melindungi pekerja ojek online. Kata kunci: Ojek online, mitra, pekerja, gig worker.   Abstract The existence of online motorcycle taxis still raises debate, whether they are workers or partners. In the decision by the U.K. Supreme Court, online motorcycle taxi workers, also known as gig workers, have been decided as workers. The results of the study indicate that Indonesian laws and regulations have not been able to accommodate the existence of online motorcycle taxis as workers. However, protection needs to be made for online motorcycle taxi partners, especially in terms of safety and security as well as income. The government needs to determine the direction of employment policies to protect online motorcycle taxi workers. Keywords: online motorcycle taxi, partners, workers, gig workers.